The Coli Surface Antigen CS3 of Enterotoxigenic Escherichia coli Is Differentially Regulated by H-NS, CRP, and CpxRA Global Regulators - Ares, Miguel A.; Abundes-Gallegos, Judith; Rodríguez-Valverde, Diana; Panunzi, Leonardo G.; Jiménez-Galicia, César; Jarillo-Quijada, Ma. Dolores; Cedillo, María Lilia; Alcántar-Curiel, Marìa D.; Torres, Javier; Girón, Jorge A.; De la Cruz, Miguel A. (Frontiers in Microbiology, 2019)
Enterotoxigenic Escherichia coli produces a myriad of adhesive structures collectively named colonization factors (CF). CS3 is a CF, which is assembled into fine wiry fibrillae encoded by the cstA-H gene cluster. In this work we evaluated the influence of environmental cues such as temperature, osmolarity, pH, and carbon source on the expression of CS3 genes. The transcription of cstH major pilin gene was stimulated by growth of the bacteria in CFA broth at 37oC; the presence of glycerol enhanced cstH transcription, while glucose at high concentration, high osmolarity, and the depletion of divalent cations such as calcium and magnesium repressed cstH expression. In addition, we studied the role of H-NS, CpxRA, and CRP global regulators in CS3 gene expression. H-NS and CpxRA acted as repressors and CRP as an activator of cstH expression. Under high osmolarity, H-NS and CpxRA were required for cstH repression. CS3 was required for both, bacterial adherence to epithelial cells and biofilm formation. Our data strengthens the existence of a multi-factorial regulatory network that controls transcription of CS3 genes in which global regulators, under the influence of environmental signals, control the production of this important intestinal colonization factor.